Proceso de adquisiciones de bienes y servicios y su relación con la gestión administrativa de la Dirección Regional de Transportes y Comunicaciones de Loreto 2021 - Meza Levy, Ricardo (2023)
The purpose that has led to the development of the research was to determine the relationship between the process of acquisition of goods and services and the administrative management of the regional direction of transport and communications of Loreto 2021. With an applied type study method, descriptive level - correlation and non-experimental design, made up of a population of 467 people, obtaining a sample of 261 workers, these people being surveyed using a questionnaire to record their perception. It was concluded that the process of acquisition of goods and services in the DRTC Loreto is perceived as regular (26%), because the needs of the institution are rarely taken into account for the programming of the requirements, sometimes it complies with the contracting regulations, likewise, the personnel is rarely trained and sometimes a quality control is carried out. On the other hand, the administrative management in the DRTC is regular (24%), since the institutional goals or objectives are sometimes well defined and clear, likewise, the technological devices available to the institution are not updated. Then the correlations were determined, that is, there is a significant relationship between the process of acquiring goods and services and administrative management, corroborated by a coefficient and a sig. of r= 0.675; p=0.000, considerable positive. Likewise, for the planning dimension, a coefficient and a sig. from r=0.613; p=0.000 considerable positive. For the organization dimension, a coefficient and a sig. from r=0.599; p=0.000, medium positive. Likewise, the direction dimension had a coefficient and a sig. from r=0.629; p=0.000, considerable positive. Finally, the control dimension obtained a coefficient and a sig. from r=0.547; p=0.000, medium positive. All the results are significantly related to worker satisfaction.